PERTUMBUHAN DAN HASIL TANAMAN BAWANG DAUN (Allium fistulosum L.) PADA BERBAGAI DOSIS PUPUK KANDANG AYAM - Budirokhman, Dodi (Agroswagati : Jurnal Agronomi, 2025)
The purpose of this study was to determine the effect of dosage chicken manure on the growth and the yield of onion (Allium fisyulosum L.) cultivars Mani'is. The experiment was conducted in lowland Jalaksana village Babakanmulya District, Kuningan regency. Research sites have clay type, pH 5,78, temperature of 200C - 270C, altitude 654 m asl (above sea level), 80% humidity, rainfall 2030 mm / year and the sun shines 12 hours / day. When the study was conducted in April 2013 to June 2013. The method used is an experimental method using a randomized block design (RBD). Dosage treatment factor is that chicken manure consists of 6 levels, namely: 0 ton/ha, 4 ton/ha, 8 ton/ha, 12 ton/ha, 16 ton/ha and 20 ton/ha. Variables observed were plant height, number of leaves, number of tillers, fresh weight per hill and fresh weight per plot. The results showed that chicken manure dosage treatment effect on plant height of 35 and 42 days after planting, YIELD number 28 after day planting, tiller number 28 after day planting, fresh weight per hill and fresh weight per plot. The treatment dosage of chicken manure 12 ton/ha yield the highest plant height is 42,5 cm at age 35 after day planting, 50,5 cm at the age of 42 after day planting, and weight of 0,8 kg/plot which is equivalent to 4 ton/ha.